Possibilities for teaching the technical conceptual knowledge of handball in a didactic unit based on Sport Education - Servilha de Lucca, Mateus Henrique [UNESP]; Impolcetto, Fernanda Moreto [UNESP]; Ginciene, Guy (Federacion Espanola Asoc Docentes Educacion Fisica-feadef, 2022)
This paper aims to implement a Didactic Unit (DU) based on Sport Education for the teaching of technical conceptual knowledge of handball, in order to know the possibilities and difficulties of this process. There were 22 classes structured based on the main characteristics of the model, with the participation of 40 students from a high school second year class. For data collection, Field Diary and focus group were used, which were subsequently submitted to thematic analysis for discussions. The DU based on Sport Education was shown as a possibility to raise awareness of the teaching and learning process of the conceptual knowledge of handball, adapting the model's characteristics to the Brazilian school reality. It is conduded that through adaptations, the model allows transformation in pedagogical practice, therefore, it is suggested to use it to innovate the teaching of sports in school, breaking with the traditional model.
Keywords: sport; school; physical education; high school; learning